THE PACE OF REFORM MANAGEMENT SYSTEM ON THE RAILWAYS OF SOME COUNTRIES IN THE WORLD - Teslenko, T. V. (Science and Transport Progress, 2003)
The contents of the article envisage an analysis of the rates of railway transport managerial structures reformation in Germany, Poland and Russia.